Role-Playing Simulations for Resilient Healthcare Systems: Lessons from Pharmaceutical Management in Puskesmas and Pustu - Anatasya Eka Purwitasari, Anatasya Eka Purwitasari; Anjelita, Bunga Destiana; Auliamanda, Nabila Luthfi; Revalia Nafisa Zahra, Revalia Nafisa Zahra; Humairo, Mika Vernicia (Tarqabin Nusantara Group, 2025)
Drug governance in Puskesmas (Community Health Centers) and Pustu (Sub-Health Centers) often faces challenges such as stockouts, expired medications, and improper storage. This study evaluates the effectiveness of a participatory role-playing simulation in enhancing healthcare workers’ competencies in pharmaceutical management. The method involved 8 groups (3–4 participants per group) engaging in diverse scenarios, including essential drug shortages and logistical coordination. Each group simulated problem-solving within a 5-minute timeframe, followed by reflective discussions to identify challenges and solutions. Results showed significant improvements: drug availability increased from 60% to 90%, expired drugs decreased from 25% to 5%, and patient satisfaction rose by 35%. Technology, such as a drug management information system (SIMO), reduced human error, though budget constraints and staff resistance emerged as barriers. Recommendations include strengthening continuous training, adopting hybrid systems (digital-manual), and advocating for policy-level funding. The simulation demonstrated that participatory approaches and appropriate technology enhance primary healthcare resilience while highlighting the need for multi-stakeholder collaboration to ensure sustainable drug governance.